O leksyce i frazeologii Dyszkursu o grzechách szostego przykazánia Bożego… Adama Gdacjusza - Haas, Agata (Forum Lingwistyczne, 2019)
The article analyses the vocabulary and phraseology of Dyszkurs o grzechách szostego przykazánia Bożego… written by Adam Gdacjusz, the Kluczbork clergyman. The text was published in 1682 in Jan Krzysztof Jakub’s printing press in Brzeg. Gdacjusz is qualified as the 17th century representative of the Silesian Polish. In this particular text he writes about the issue of promiscuity, adultery and sinuous conduct. The lexis and phraseology of the Dyszkurs… is characterised by explicit expressiveness, vividness and diversity. The author is known for his rapid style of rhetoric and crudeness that he achieves by the careful selection of words, with which he strikes the reader emphasising the brutal power hidden within them. Such a method requires frequent repetitions, rehashes, and a peculiar kind of redundancy, especially in the case of exempla. The text surprises the reader with the multitude of names associated with human sexual life. Gdacjusz enumerates and discusses the reasons for prostitution, yielding to the sin of dissoluteness, and immoral conduct. The colourfulness and vividness of the Kluczbork preacher’s text is also influenced by the various idiomatic expressions, sayings, proverbs and numerous colloquialisms taken directly from the language spoken by the Kluczbork dwellers of that time. Lexis built in this way adds authenticity and expression to his deliverance. What is important, some words and idioms still function today. In his sermons, Gdacjusz both fulfils the requirements of the preacher’s rhetoric and links simplicity with sophistication on the lexical layer. A sublime and elevated style of his utterance interweaves with the sharp, plain, and sometimes even coarse tone of preaching. Therefore, Adam Gdacjusz’ oeuvre stands out from other Silesian preachers and contributes significantly to the 17th-century Silesian Protestant literature.